Fetoplacental regional variations in the expression of angiopoietin-1, angiopoietin-2, and Tie2 in normal-term and near-term pregnancies. (1st November 2016) - De, Alok; Maulik, Dev; Lankachandra, Kamani; Mundy, David Christopher; Ye, Shui Qing; Gerkovich, Mary M.
Abstract: Background : Angiopoietin-1 (Ang1), angiopoietin-2 (Ang2), and the receptor tyrosine kinase with immunoglobulin-like and EGF-like domains 2 (Tie2) are known to be involved in fetoplacental angiogenesis adequacy, which is a primary determinant of fetal growth. Regional variations in Ang1, Ang2, and Tie2 remain unknown, although fetoplacental vascularity and gene expressions differ between the placental center and the periphery. Objective : The aim of this study was to test the hypothesis that there are regional variations in the expression of these angiopoietins in human placentas from uncomplicated term and near term pregnancies. Study design : In this prospective study, central and peripheral samples were collected from fresh placentas from normal-term and near-term pregnancies delivered by Cesarean section ( n = 7, 36–41 week gestation) prior to the onset of labor. Regional differences in Ang1, Ang2, and Tie2 protein expressions were measured by Western blot and densitometric analyses with b-actin normalization, and their fetoplacental regional localization assessed by immunohistochemistry. The Ang1 and Ang2 ratios at central and peripheral sites were determined. Statistical analysis was performed using Student's t -test. Results : Ang1 protein expression was higher in the placental periphery than in the center (2.48 ± 0.42 versus 1.74 ± 0.27, p = 0.01). In contrast, Ang2 protein expression was greater in the placental center than in the periphery (10.10 ± 1.82 versus 7.15 ± 1.12, respectively, p = 0.03). The Ang1–Ang2 ratio reflected these differential expressions. Tie2 protein expression was higher in the placental periphery than in the center (0.21 ± 0.02 versus 0.16 ± 0.02, p = 0.003). The immunoreactivity of Ang1 and Tie2 was stronger in the periphery than in the center, and that of Ang2 was stronger in the center than in the periphery. Conclusions : Ang1, Ang2, and Tie2 are differentially expressed in placental center and periphery. Ang1/Ang2 ratio reflects this regional variation in the angiogenic balance that has implications for fetoplacental villous angiogenesis. The results also demonstrate the importance of considering the location of placental sampling sites for any future investigations of fetoplacental villous angiogenesis.